Cayyene pepper: structure and supply chain performance in Gorontalo Province, Indonesia. Issue 1 (March 2020) - Indriani, R; Darma, R; Musa, Y; Tenriawaru, A N; Mahyuddin
Abstract: The research aims to examine the structure and performance of the cayenne pepper supply chain. The study was conducted in Gorontalo from January to March 2019. The research was using the survey method. Data analysis was using descriptive and marketing efficiency analysis. The results showed 1) The structure of the cayenne pepper supply chain in Gorontalo Province consists of seven distribution channels. Sale of cayenne pepper by farmers through collectors (40 percent), wholesalers (26.67 percent), market traders (10 percent), and retailers (23.33 percent). The primary members of the cayenne supply chain consist of farmers, collectors, wholesalers, out-of-town traders, market traders, retailers, consumers, and agroindustries. The secondary members are farm shops, banks, transportation service providers, the Agriculture Service, and information media. 2) The most efficient distribution channel is channel six because the smallest marketing efficiency value is 3.17 percent. The cayenne pepper's market in Gorontalo runs inefficiently because it has a price transmission elasticity value of 1.11 (Et> 1). It means the rate of change in prices at the consumer level is greater than the rate of change in prices at the farmer's level.